Critical appraisal of evidence for anti-Xa monitoring and dosing of low-molecular-weight heparin in renal insufficiency. Issue 10 (3rd October 2022) - van den Broek, M. P. H.; Verschueren, Marjon V.; Knibbe, C. A. J.
ABSTRACT: Introduction: Several guidelines advise to monitor therapeutic LMWH therapy with peak anti-Xa concentrations in renal insufficiency with subsequent dose adjustments. A better understanding of the clinical association between peak anti-Xa concentrations and clinical outcomes is mandatory, because misunderstanding this association could lead to erroneous, and potentially even harmful, LMWH dose adjustments Areas covered: We reviewed the evidence of the widely applied therapeutic window for anti-Xa peak concentrations and report on the evidence for pharmacokinetic dose reduction in renal insufficiency, limitations of peak and trough anti-Xa concentration monitoring. Expert opinion: The added value of peak anti-Xa monitoring in patients with renal insufficiency, receiving a dose reduced for pharmacokinetic changes, is not supported by data. Enoxaparin and nadroparin should be adjusted to 50–65% and 75–85% of the original dose for patients with a creatinine clearance (CrCL) of <30 ml/min and 30–60 ml/min, respectively. Tinzaparin should be adjusted to around 50% of the original dose for patients with a CrCL of <30 ml/min. In case anti-Xa monitoring is applied, trough concentration anti-Xa monitoring is preferred over peak monitoring, aiming at a maximum concentration of 0.4 IU/mL for once-daily dosed tinzaparin and 0.5 IU/mL for twice-daily dosed enoxaparin and nadroparin.